Cognitive Exploration of Mathematics Teachers in the Lesson Study Model Through Metacognitive Skills to Enhance Digital Competence in Independent Learning - Hidajat, Djatmiko; Susilowati, Dewi; Exata, Anisa Prima; Hadiprasetyo, Krisdianto (Universitas Islam Negeri Sunan Kudus, 2024)
This research aims to explore the cognition of mathematics teachers through the lesson study model focusing on metacognitive skills and digital competence. The background of this research is based on the urgency of improving learning evaluation. Although many studies have been conducted, however these studies have yet to specifically explore teachers' cognition before, during, and after the lesson. Therefore, this research focuses on the three stages of lesson study: plan, do, and see. This research method uses a qualitative approach to reveal the cognition of mathematics teachers. The study involves two subjects: a male model teacher and a female model teacher with ten observers. Data were collected using initial diagnostic tests, observations, and reflections with the students. The research results show that teachers have a good understanding in learning objectives, teaching strategies that align with student characteristics, and digital skills. The data for this research was collected using a four-step metacognitive skills method, namely: prediction, planning, monitoring, and evaluation. The objectives of this research are: 1) The formation of cognitive classifications of teachers in three stages: a) Plan, where teachers conduct initial analysis, understand student characteristics, and prepare lesson plans; b) Do, where teachers implement the prepared lesson plans using predetermined methods and strategies according to the material and student characteristics, and actively interact with students to collect learning data; and c) See, where teachers evaluate student learning outcomes, reflect on the learning process, identify successes and shortcomings in teaching, and improve teaching practices based on the reflection of the obtained data. 2) Lesson study has a positive impact by supporting the availability of data for researchers in the data collection process, as well as enhancing teachers' digital competence. Penelitian ini bertujuan menggali pemahaman kognitif guru matematika melalui model Lesson Study dengan fokus pada keterampilan metakognitif dan kompetensi digital. Latar belakang penelitian ini didasarkan pada urgensi evaluasi pembelajaran untuk perbaikan di pembelajaran berikutnya. Meskipun banyak penelitian telah dilakukan, belum ada yang secara khusus mengeksplorasi pemikiran guru sebelum, selama, dan setelah pembelajaran. Oleh karena itu, penelitian ini berfokus pada tiga tahap Lesson Study: Plan, Do, dan See. Metode penelitian melibatkan dua subjek: seorang guru model laki-laki dan seorang guru model perempuan dengan sepuluh observer. Data dikumpulkan melalui tes diagnostik awal, observasi, dan refleksi bersama peserta didik. Hasil penelitian menunjukkan bahwa guru-guru memiliki pemahaman yang baik tentang tujuan pembelajaran, strategi pengajaran yang sesuai dengan karakteristik peserta didik, dan keterampilan digital. Data penelitian ini menggunakan metode empat langkah keterampilan metakognitif yaitu: prediksi, perencanaan, monitoring, dan evaluasi. Tujuan penelitian ini adalah: 1) Terbentuknya klasifikasi kognitif pengajar di tiga zona waktu: a) Plan, di mana pengajar melakukan analisis awal, memahami karakteristik siswa, dan mempersiapkan rencana pembelajaran; b) Do, pengajar melaksanakan rencana pembelajaran yang telah disusun, menggunakan metode dan strategi yang sudah ditentukan sesuai dengan materi dan karakteristik siswa, dan pengajar aktif berinteraksi dengan siswa dalam mengumpulkan data pembelajaran; dan c) See, pengajar mengevaluasi hasil belajar siswa dan merenungi proses pembelajaran, mengidentifikasi keberhasilan dan kekurangan dalam mengajar, dan memperbaiki praktik mengajar berdasarkan refleksi data yang diperoleh. 2) Lesson Study memberikan dampak positif yaitu mendukung ketersediaan data bagi peneliti dalam proses terkumpulnya data riset, serta meningkatkan kompetensi digital pengajar.